Constructing interorganizational collaboration: The action researcher as boundary subject - Huzzard, Tony; Ahlberg, Beth Maina; Ekman, Marianne (Action research (London, England), 2010)
This article aims to explore critically the role of an action research team in the social construction of interorganizational collaboration aimed at transgressing organizational and professional boundaries. We argue that the new relationships, actor conceptions and in some cases forms of work organization arising from the change process have been socially constructed through the discursive interventions of the researchers. This has largely occurred through informal interaction with and between the actors engaged in the development process. The action researcher, rather than being a neutral discursive gatekeeper in collaborative development projects, is an active constructor of the discourse shaping the collaboration. A case is presented showing how the researcher role is thus better seen as being an active boundary subject mediating across various professional and organizational perspectives rather than a passive boundary object. Accordingly, by focusing on the discursive role of active researchers as boundary subjects, we can reflect more critically on the roles we adopt in our intervention endeavours and their inevitably political nature.